Childhood survivors of high‐risk neuroblastoma show signs of immune recovery and not immunosenescence. Issue 12 (18th August 2020) - Lázničková, Petra; Kepák, Tomáš; Hortová – Kohoutková, Marcela; Horváth, Luděk; Sheardová, Kateřina; Marciniak, Rafal; Vacca, Carmine; Šiklová, Michaela; Zelante, Teresa; Rossmeislová, Lenka; Křenová, Zdenka; Štěrba, Jaroslav; et al.
Abstract : Neuroblastoma survivors show signs of immunosenescence early after therapy in CD8 + T cell compartment and elevated plasma TNF‐α but in later follow‐up immune recovery comes into play. Whether the recovery phenotype is long lasting or transient remains to be elucidated, however, late adverse effects often occur in childhood cancer survivors.